On Solving Some Fifth Order Nonlinear PDEs Using The Modified Kudryashov Method - Alurrfi, Khaled A. E.; Attaweel, Mohammed E. H. (The Libyan Journal of Science, 2022)
In this paper , the modified Kudryashov method was applied to construct the exact travelling wave solutions for some fifth order nonlinear partial differential equations (PDEs), namely, the Kaup-Kupershmidt, the Ito, the Caudrey-DoddGibbon, the Lax and the Sawada-Kotera equations.